Report on the Bench Mark Survey of Bhadrak Community Development Project Block I Orissa 1956 - Planning Commission (Planning Commission, 1956)
Objective-Among the objectives of evaluation work undertaken by the programme Evaluation Organisation, two of the more important arc-(i) assessment of the extent of adoption of improved practices advocated by the community development and national extension programmes and (ii) obtaining insight into the impact of these programmes upon the economic and social life of the rural people. The field officers of the organisation had been making observations on these two aspects in their periodic reports from the time they were posted in the field in May 1953. However, considering the importance of detailed and precise information on these aspects for a proper assessment of the impact of development programmes it was felt that a series of special surveys, should be undertaken in all the evaluation centres for this purpose. Through this initial survey called the Bench Mark Survey (B. M. S.) the position regarding acceptance of sponsored practices and certain aspects of the rural economy related to the development programme would be ascertained as at the time of the survey or for a given period immediately before it. From this base or ‘benchmark’ position, the changes occurring in the area during the course of operation of the projects would be measured by means of repeat surveys undertaken at specified intervals.
Planning Commission, Programme Evaluation Organisation
Planning Commission, Programme Evaluation Organisation